Dual equation and inverse problem for an indefinite Sturm–Liouville problem with m turning points of even order - Marasi, Hamidreza; Akbarfam, Aliasghar Jodayree (Mathematical Modelling and Analysis, 2012)
In this paper the differential equation y″ + (ρ 2 φ 2 (x) –q(x))y = 0 is considered on a finite interval I, say I = [0, 1], where q is a positive sufficiently smooth function and ρ 2 is a real parameter. Also, [0, 1] contains a finite number of zeros of φ 2 , the so called turning points, 0 < x 1 < x 2 < … < x m < 1. First we obtain the infinite product representation of the solution. The product representation, satisfies in the original equation. As a result the associated dual equation is derived and then we proceed with the solution of the inverse problem.